2014
DOI: 10.1002/cphc.201402316
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Design of an Endohedral Heteronuclear Dimetallofullerene (UGd)@C60 with Exceptional Structural and Electronic Properties

Abstract: Ever since the first synthesis of La@C82 and U@C28 , there has been a growing interest in the study of endohedral metallofullerenes (EMFs) because of their great potential in various applications. Here we design a novel heteronuclear EMF (U-Gd)@C60 , by using density functional theory (DFT), which shows an encapsulation energy of about -5.53 eV, comparable to that of U2 @C60, La2 @C80 , and Lu2 @C76 . (U-Gd)@C60 is found to have a surprising twofold, single-electron UGd bond that results from the strong nanoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] In particular, computational studies have disclosed the exceptional structural and bonding natures of uranium EMFs. [30][31][32][33][34][35] Significantly, Wang et al more recently prepared a large family of Th@C 2n (2n 5 74-96) by a modified arc discharge method, and for the first time, they successfully isolated Th@C 82 and unambiguously characterized its structure as Th@C 3v (8)-C 82 by X-ray crystallographic analysis. [36] Interestingly, compared with the conventional divalent or trivalent lanthanide EMFs, it exhibits an unprecedented four electrons transfer from a single metal atom to the cage and its electronic structure is thus described as Th 41 @C 42 82 .…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] In particular, computational studies have disclosed the exceptional structural and bonding natures of uranium EMFs. [30][31][32][33][34][35] Significantly, Wang et al more recently prepared a large family of Th@C 2n (2n 5 74-96) by a modified arc discharge method, and for the first time, they successfully isolated Th@C 82 and unambiguously characterized its structure as Th@C 3v (8)-C 82 by X-ray crystallographic analysis. [36] Interestingly, compared with the conventional divalent or trivalent lanthanide EMFs, it exhibits an unprecedented four electrons transfer from a single metal atom to the cage and its electronic structure is thus described as Th 41 @C 42 82 .…”
Section: Introductionmentioning
confidence: 99%
“…Hypothetical U 2 @C 70 and U 2 @C 84 fullerenes were calculated therein 45 but the U-U bonding in these systems was not investigated, possibly because of the calculated large U-U separation, r U-U ~ 3.9 Å. 47 Studies of U 2 @C 61 revealed that the exohedral carbon atom has a strong influence on the U-U distance and ground-state spin multiplicity. 46 Recent study has predicted the UGd@C 60 analogue of U 2 @C 60 fullerene to have a large encapsulation energy and a high-spin 11-et ground state with a twofold one-electron U-Gd bond.…”
Section: Introductionmentioning
confidence: 99%
“…Dai et al predicted that in hypothetical U 2 @C 90 , the uranium atoms separate to r U-U ~ 6.1 Å. 47,48 Endohedral metal-metal bonding has been recently discussed in some experimentally known lanthanide and transition-metal fullerenes, for example, in Y 2 @C 79 N, 49 Lu 2 @C 76 , [50][51][52] and anionic La 2 @C 80 fullerenes. 47 Studies of U 2 @C 61 revealed that the exohedral carbon atom has a strong influence on the U-U distance and ground-state spin multiplicity.…”
Section: Introductionmentioning
confidence: 99%
“…Thus DFT is a common tool to study system containing heavy elements. [18,26,27,56] The 3-21G, 6-31G, 6-31G*, 6-311G*, cc-pVDZ, and aug-cc-pVDZ basis sets were used for B atoms. [54] The relativistic effective core pseudopotential (RECP) could take scalar relativistic effects into account reasonably well and meanwhile save the computation time.…”
Section: Computational Techniquesmentioning
confidence: 99%
“…[54] The relativistic effective core pseudopotential (RECP) could take scalar relativistic effects into account reasonably well and meanwhile save the computation time. [18,26,56] Therefore, the spin-orbit coupling effect is omitted in this study. [18,26,27,56] The 3-21G, 6-31G, 6-31G*, 6-311G*, cc-pVDZ, and aug-cc-pVDZ basis sets were used for B atoms.…”
Section: Computational Techniquesmentioning
confidence: 99%